Sharia Compliance, Islamic Corporate Governance, Intellectual Capital, and Earning Management toward Financial Performance in Indonesia Islamic Banks - Munifatussa'idah, Asma' (Ekonomi Syariah IAIN Kudus, 2021)
This research aims to analyze the effect of Sharia Compliance, Islamic corporate Governance, Intellectual Capital, and Earnings Management toward the Financial Performance of Islamic Banks. The research method uses a quantitative approach with secondary data. Data were obtained from 12 (twelve) Islamic Commercial Banks in Indonesia, which were selected using the purposive sampling technique. The analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that Sharia compliance has an effect on the financial performance of Islamic banks. Islamic corporate governance has an effect on earnings management and financial performance of Islamic banks, and intellectual capital has an effect on the financial performance of Islamic banks. Meanwhile, earnings management has no effect on the financial performance of Islamic banks. The findings of this study provide evidence that the variables of Sharia compliance, Islamic corporate governance, and intellectual capital can help Islamic banks in Indonesia improve their financial performance. In addition, these findings will contribute to the literature on the determinants of Islamic bank financial performance.